2020
DOI: 10.3390/e22070737
|View full text |Cite
|
Sign up to set email alerts
|

Observable and Unobservable Mechanical Motion

Abstract: A thermodynamic approach to mechanical motion is presented, and it is shown that dissipation of energy is the key process through which mechanical motion becomes observable. By studying charged particles moving in conservative central force fields, it is shown that the process of radiation emission can be treated as a frictional process that withdraws mechanical energy from the moving particles and that dissipates the radiation energy in the environment. When the dissipation occurs inside natural (eye)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Thus, it becomes understandable why just the simplest mathematical regularities such as Fibonacci series [13][14][15][16][17]87] and symmetrical patterns are abundant in biology; these regularities decrease the algorithmic complexity of biological systems [33]. The informational paradigm of biology is closely related to the Landauer Principle bridging theory of information of physics and suggesting the thermodynamic equivalent of information, under establishing the lower theoretical limit of energy consumption of biological computation [35][36][37][89][90][91][92][93][94][95][96][97][98][99]. The analyses of the computational efficiency of bacteria demonstrated that as bacteria become larger their overall translational efficiency converges on that of a single ribosome [106].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it becomes understandable why just the simplest mathematical regularities such as Fibonacci series [13][14][15][16][17]87] and symmetrical patterns are abundant in biology; these regularities decrease the algorithmic complexity of biological systems [33]. The informational paradigm of biology is closely related to the Landauer Principle bridging theory of information of physics and suggesting the thermodynamic equivalent of information, under establishing the lower theoretical limit of energy consumption of biological computation [35][36][37][89][90][91][92][93][94][95][96][97][98][99]. The analyses of the computational efficiency of bacteria demonstrated that as bacteria become larger their overall translational efficiency converges on that of a single ribosome [106].…”
Section: Discussionmentioning
confidence: 99%
“…93-94. Extension of the Landauer Principle to the realms of quantum mechanics [95] and general relativity [96] were reported. The Landauer Principle applied to mechanical motion demonstrates that dissipation of energy is the key process through which mechanical motion becomes observable [97]. The analysis of performance of photon detectors (such as eyes) brings to the conclusion that just efficiency that is limited the Landauer energy bounds on information gain and information erasure [98].…”
Section: Symmetry and Ordering In Biological Systems And The Landauer...mentioning
confidence: 99%
“…We continue the development of the research program introduced by John Archibald Wheeler, suggesting that the basic notions of physics are deeply rooted in the theory of information [1]. We address the Gedanken experiments, combining the ideas emerging from the Einstein Principle of Equivalence [23][24][25][26][27] and the Landauer Principle [11][12][13][14][15][16][17][18][19][20][21][22]. For this purpose three experimental systems embedded into the free falling Einstein elevator are addressed, namely: the double well system containing particle m, the free jointed polymer chain with the mass m attached to the chain, and the minimal Szilard engine driven by a single particle m. When the particle m is confined within the free falling doublepotential-well system, representing the binary logics, it may be transferred from position "ZERO" to position "ONE", by an infinitesimal horizontal force.…”
Section: Discussionmentioning
confidence: 99%